Archaeological Data Patterns Through Statistical Analysis: Jambi Ancient Graves, Indonesia - Nengsih, Titin Agustin; Putra, Benny Agusti; Andhifani, Wahyu Rizky; Husni, Amir (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study explores tombstone characteristics to reveal socio-cultural patterns of past societies, particularly in ancient Jambi. Traditional archaeology often relies on qualitative methods, which can overlook underlying patterns in the data. This research addresses that gap by integrating quantitative analysis, specifically cluster analysis, to complement and enhance qualitative interpretations. Using primary data from 50 graves, which include both categorical and continuous variables, the study identifies relationships among tombstone features and classifies them into five distinct clusters. These clusters reflect variations in socio-economic status and illuminate burial practices and cultural traditions of the time. By combining qualitative and quantitative approaches, the research offers a more holistic view of historical contexts and social stratification. The findings underscore the importance of using mixed data clustering in archaeology to uncover patterns that may not be visible through conventional methods alone. This methodological innovation contributes to improving archaeological research practices in Indonesia and has the potential to inform future studies across cultural and historical contexts. Overall, this research not only deepens our understanding of the social fabric of ancient Jambi but also paves the way for broader applications of data-driven approaches in cultural heritage and archaeological investigations.